A User Mobility Broadband Spectrum Aggregation Applications in LTE-Advance Heterogeneous Wireless Network Systems Using Real-Time Spectrum Selection Framework - Nkeleme, V. O.; Udo, E. U.; Okoro, C. K.; Oborkhale, L. I.; Odo, K. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2024)
Mobile user equipment can benefit from increased bandwidth and radio coverage of various access technologies through carrier aggregation and integration of heterogeneous networks. However, because of the mobility of user equipment, these technologies have increased the frequency of handoff scenarios, which results in low throughput and a high outage probability. In order to enable users to move between cells without losing connections, handover is an essential part of mobility management. However, no lone access mechanism can provide seamless and delay-free seamless interaction. As a result, the development of a suitable handover decision algorithm is necessary to ensure excellent service continuity and dependable user equipment access to the network at any location and at any moment. To confirm if various handover choice algorithms are effective in preventing communication failures and enhancing system performance. This research produced a mathematical model for the Real-Time Spectrum Selection Framework and Handover Decision Algorithm (RSSF-HDA). Additionally, mathematical models were extracted for comparison between the Multi-influenced Handover Decision Algorithm (MIF-HDA) and the Conventional Handover Decision Algorithm (Conv-HDA). A statistical comparative study was carried out using data from MTN drive-test readings at the Low-Cost housing estate located in Abesan, Ipaja, Lagos. According to statistical analysis results, the Real-Time Spectrum Selection Framework and Handover Decision Algorithm enhance system performance in terms of Cell edge Spectral Efficiency, and user throughput when compared with multi-influenced handover Algorithm and MTN field readings. For cell edge Spectral Efficiency at an average speed of 80km/s, RSSF-HDA gave a value of 1.52 bits/Hertz compared to MIF-HDA and MTN field readings with values of 1.37bits/Hertz and 1.33bits/Hertz respectively. For user throughput, inferred that there is no significant difference in readings of system throughput from the MTN field readings, MIF-HDA, and simulated RSSF-HDA which were 31%, 33%, and 34% respectively.